Lived Experiences of Young Adults From Broken Families on Marital Relationships - Falculan, Raymund Madrigal; Paula, Paula A; Ocdamia, Jon Joshua J; Samiley, Samantha Gaylle G (11th International Scholars Conference, 2019)
People often take for granted the impact of having separated parents on children. Individuals from broken homes are highly impressionable and the effects of what they have witnessed during childhood are conventionally carried with them into adulthood. There have been a limited amount of studies describing the impact of parental separation of young adults’ perception on marriage. This study aimed to delve into how parental separation affects young adults’ perception on marital relationship. Specifically, this study deals with the perception on marital relationships of young adults from broken families. Also, it explores the outlook on marital relationships of young adults from broken families after their parents’ separation. This study used a phenomenological research design to explore young adults’ perception on marriage. A total of 12 young adults coming from broken families participated in the study to provide the researchers with information about their thoughts and feelings about marriage. The researchers used a semi-structured interview and the collected data were analyzed using the Colaizzi’s method. On the perception on marital relationship of young adults from broken families, four themes emerged, namely: God-centered relationship; couples in love; legalization of a relationship; and foundation of family. The participants defined that perception of marital relationships is related to the definition of a healthy relationship between husband and wife. Furthermore, the factors that affect the outlook of young adults from broken families were categorized into four themes: negative experience leading to fear, development of trust issues, poor self-worth, and attachment problems. Here, the participants explained that the negative outlook on marital relationships is related to the negative experiences, trust issues, poor self-worth, and attachment issues that developed as impact of broken families. The researchers recommend that similar studies with a quantitative approach be conducted for the further assessment of the dilemma presented by the study. Further research could bring about different results especially if done on a large population and different.